Natural Disaster, Policy Action, and Mental Well-Being: The Case of Fukushima - Jan Goebel; Christian Krekel; Tim Tiefenbach; Nicolas R. Ziebarth (Institute for the Study of Labor (IZA), 2013)
We study the impact of the Fukushima disaster on people's mental well-being in another industrialized country, more than 5000 miles distant. The meltdown significantly increased environmental concerns by 20% among the German population. Subsequent drastic policy action permanently shut down the oldest nuclear reactors, implemented the phase-out of the remaining ones, and proclaimed the transition to renewables. This energy policy turnaround is largely supported by the population and equalized the increase in mental distress. We estimate that during the 3 months after the meltdown, Fukushima triggered external monetized health costs worth 250 per distressed citizen particularly among risk averse women.
Keywords: I18; I31; Z13; Q54; 330; Fukushima; meltdown; nuclear phase-out; mental health; environmental worries; SOEP